The maritime heritage of the Cayman Islands - Smith, Roger C., 1949- (New perspectives on maritime history and nautical archaeology., 2000)
"Roger C. Smith follows the mysterious tracks of the sea turtles and the mariners who hunted them, from the shores of the Caymans to the coastal lagoons of Cuba and finally to the Miskito Cays of Nicaragua. He also pursues the colonial exploits of privateers and pirates, examines the development of island catboats and schooners, and takes the reader underwater to the sites of unlucky ships that wrecked on poorly charted reefs. As archaeological sites and diving attractions, sunken ships continue to share a central role in today's Caymanian maritime perspective." "Blending elements of geography, archaeology, and ethnography, this history offers a portrait of all aspects of Caymanian nautical traditions."--Jacket.